Mulching influences pear yield and quality by changing rhizosphere microbial community structure in the arid region of Northwest China - Li, Hongxu; Li, Peigen; Cao, Gang; Zhao, Mingxin; Zhu, Zhiyi; Ma, Yanwei; Wang, Wei; Cao, Sufang; Xu, Yangchun; Dong, Caixia (Frontiers in Plant Science, 2025)
IntroductionMulching is widely adopted in pear orchards to improve soil quality and fruit production, yet its effects on rhizosphere microbial communities and the mechanisms linking soil–microbe interactions to pear yield and quality remain poorly understood.MethodsA field experiment was conducted in a pear orchard located in the arid region of Northwest China. Three treatments were applied: no mulching (CK), plastic film mulching (FM), and straw mulching (SM). Soil physicochemical properties were analyzed, and rhizosphere microbial community characteristics were assessed using high-throughput sequencing of 16S rRNA and ITS. Network analysis and multivariate statistical approaches were employed to explore microbial community structure, ecological modules, and their relationships with soil properties and fruit traits.ResultsBoth FM and SM significantly improved pear yield and fruit quality compared with CK. Principal coordinate analysis showed that mulching significantly altered soil microbial community structure. Proteobacteria and Acidobacteria dominated the bacterial community, while Ascomycota was the predominant fungal phylum. FM increased the abundance of Gram-negative bacteria and reduced Gram-positive groups. Network analysis indicated that FM enhanced ecological modules enriched in indicator species positively correlated with yield and sugar/acid ratio. Soil moisture, nutrient content, and organic matter were identified as major drivers of yield and fruit quality.DiscussionThese findings demonstrate that mulching improves pear yield and quality by modifying soil properties and rhizosphere microbial networks. Plastic film mulching was more effective than straw mulching, further enhancing fruit production by improving soil nutrient content, moisture, and microbial community composition, including the recruitment of functional microbes.